From Adolescence to Motherhood: Understanding the Plight of Teenage Mothers (British Journal of Multidisciplinary and Advanced Studies, 2024)
Teenage motherhood continues to be a pressing societal issue because it significantly impacts lives of adolescent girls as they transition to motherhood. Using a qualitative transcendental phenomenology, this study explored the lived experience of senior high school teenage mothers in one of the schools in Bukidnon.  Data were collected through phenomenological in-depth interview with strict adherence to ethical principles.  The data were analyzed using Hyper Research software to determine the code, categories, and themes.  For the participants, teenage motherhood can be summarized into three emerging themes such grappling with motherhood, social dilemmas and support, and appreciating motherhood. Grappling with motherhood involved balancing family and student life, understanding the occurrence of pregnancy, and hurdling the challenge of teenage motherhood.  Furthermore, the participants as a teenage mother have to face social dilemmas and such as various family-related struggles.  However, they also received a lot of family support.  In the long run, the participants have appreciated motherhood as they became aware of the joy of motherhood as they made their dreams and contentment of the life of being a teenage mother. Based on the findings, several recommendations are proposed. The lived experience of the teenage mothers provides valuable insights about the challenges these young mothers face, the positive learning experiences they gain, and their aspirations for the future. Understanding these aspects is crucial for developing comprehensive support systems, challenging societal stereotypes, and empowering teenage mothers to navigate their roles as parents and individuals successfully. It is recommended that future researchers may conduct longitudinal research on the long-term outcomes and interventions for teenage mothers.